Il padre muto e la vocazione alla sterilità Parte seconda: la testimonianza letteraria - Testoni, Ines (Il sogno della farfalla, 2009)
The article presents the second part of a research that considers the crisis of sense that characterizes the reproductive question in the West, between the 1800s and 1900s, founded on the symbolic coordinates that link the North and the South of Europe. The basis of the research concerns the loss of sense of the paternal word, in other words the silence of the father. Through an analysis of some literary texts characterised by misogyny, interpreted through the concept of the decline of Western traditional thinking in line with E. Severino’s perspective, this second part analyses the crisis of morals. It traces signs of hatred that men show towards women, which may be considered as a cause of a great vocation to sterility. Misogyny can in fact be considered a symptom of the masculine crisis regarding procreation, linked to the resumption of traditionalism, in the expression of Pirandellism, degrading into cynicism which is the background of mafia culture, a phenomena that characterises not only Italy.